Inulinase Producing Yeast Isolated from Kepok Banana Peels (Musa acuminata x balbisiana) - Romario Dion; Wijanarka Wijanarka; Sri Pujiyanto (Biosaintifika: Journal of Biology & Biology Education, 2022)
Inulinase enzyme (EC 3.2.1.80) is an enzyme capable of hydrolyzing inulin and is used as a catalyst in the production of High Fructose Syrup (HFS) and fructooligosaccharides (FOS). Inulinase enzymes can be produced by yeasts found in waste such as kepok banana peels (Musa acuminata x balbisiana). The aims of this study were to obtain the inulinase enzyme-producing yeast from kepok banana peels and to determine the effect of commercial inulin concentration and incubation time on enzyme activity. This research was conducted experimentally using a factorial completely randomized design with factors being inulin concentration of 1% (K1), 3% (K2) and 5% (K3) and incubation time of 6th (W1), 12th (W2), 18th (W3), and 24th hours (W4). The results showed that there were 4 isolates of inulinolytic yeasts obtained from kepok banana peels, namely YP1, YP2, YP4, and YP6. However, the most potential isolate to be used in inulinase production was YP2 isolate because it had the highest inulinolytic ratio value of 1.96. The results of inulinase activity showed that only inulin substrate with concentration of 5% (K3) had a significant or significant effect on inulinase production.